A Comparative Study Installation Arrangement of Primary Flight Display (PFD) in the Flight Deck’s Regional Passenger Transport Aircraft - Prakasa, Anantia; Sophian, Indra Permana (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The Flight Deck or cockpit is designed to support the prosecution of aircraft mission. For aircraft with commercial purpose such as passenger transport aircraft, there must be good ?fit? between the human, the machine which composed of various aircraft system and the aircraft mission; and these are what the Flight Deck design process needs to ensure but not limited to display design, aircraft control, automation, HCI on the Flight Deck and pilot?s view to outside through cockpit windows namely external vision. The external vision must satisfy regulatory requirements which intended to ensure that the view is adequate for pilots to operate the aircraft safely and gives them a reasonable opportunity to see and avoid other aircraft that pose a collision threat. Concurrently during critical periods of flight, it is important that the flight crew access information in front of his view with minimal head rotation. Cockpit-Displays with critical flight information should then be located to these locations. Compromising both external vision and internal vision as Pilot?s visibility should be attained.